Comparison of spirometry data and symptoms between male and female smokers with chronic obstructive pulmonary disease - Rida Khan; Hafiz Muhamamd Waseem; Sadia Nazir; Shumaila Doggar; Mohsin Ali Cheema; Khalid Parvez Lone (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous disease, showing the exaggerated response of airways to any injurious stimulus. It is no longer considered as the disease of men as it is becoming increasingly prevalent in females. Evidence suggests that gender affects the clinical presentation of the disease. The objectives of the study is to compare spirometry data between male and female smokers with COPD and to study the association of cough, sputum, and dyspnea with gender in smokers with COPD. METHODOLOGY: This descriptive study was conducted at the University of Health Sciences Lahore. The study sample included 41 COPD patients with a history of smoking. After taking written informed consent, patients were recruited from the outpatient departments of tertiary care hospitals of Lahore by convenience sampling technique. A complete history was taken, and spirometry was done on each subject. The subjects were divided into male and female groups, followed by the comparison of Spirometry data between the groups and association of symptoms with gender using appropriate statistical techniques. RESULTS: The results of this study demonstrated females were significantly younger and exhibited a greater decline of lung functions with similar pack-years history compared to male smokers with COPD. The most common presentation of females was breathlessness compared to male patients, who had sputum production as the most common presentation. CONCLUSION: Significant differences were seen in spirometry and clinical presentation of the disease in male and female COPD groups, showing the onset and symptomology of the disease.